2014
DOI: 10.1038/nchembio.1581
|View full text |Cite
|
Sign up to set email alerts
|

A potentiator of orthosteric ligand activity at GLP-1R acts via covalent modification

Abstract: We report that 4-(3-(benzyloxy)phenyl)-2-ethylsulfinyl-6-(trifluoromethyl)pyrimidine (BETP), which behaves as a positive allosteric modulator at the glucagon-like peptide-1 receptor (GLP-1R), covalently modifies cysteines 347 and 438 in GLP-1R. C347, located in intracellular loop 3 of GLP-1R, is critical to the activity of BETP and a structurally distinct GLP-1R ago-allosteric modulator, N-(tert-butyl)-6,7-dichloro-3-(methylsulfonyl)quinoxalin-2-amine. We further show that substitution of cysteine for phenylal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 19 publications
9
86
0
5
Order By: Relevance
“…Although the diversity of GLP-1 receptor small molecule agonists may seem to support this, it is not yet clear where they each might dock, and the possibility exists that these receptors can be activated by agents acting at a variety of sites, including the intracellular face of the receptor (49). The current work has provided new insights into the natural agonist binding pocket and a key interaction that may occur there.…”
Section: Secretin Bindingmentioning
confidence: 90%
“…Although the diversity of GLP-1 receptor small molecule agonists may seem to support this, it is not yet clear where they each might dock, and the possibility exists that these receptors can be activated by agents acting at a variety of sites, including the intracellular face of the receptor (49). The current work has provided new insights into the natural agonist binding pocket and a key interaction that may occur there.…”
Section: Secretin Bindingmentioning
confidence: 90%
“…Incorporation of a cysteine at Phe-345 near the cytoplasmic side of TM6 has been shown to sensitize GCGR to the positive allosteric modulator BETP (4-(3-(benzyloxy)phenyl)-2-ethylsulfinyl-6-(trifluoromethyl)pyrimidine), leading to ligand-dependent positive allosteric activity similar to that of GLP-1R (23,24). In addition, Phe-345 is close to the binding site of the GCGR antagonist MK-0893 (Fig.…”
Section: Mutations At Phe-345 Are Sufficient To Induce Constitutive Rmentioning
confidence: 99%
“…In contrast, the pyrimidine BETP (31) was not competed by exendin(9 -39) or GLP-1 and is, therefore, thought to allosterically activate GLP-1R (31)(32)(33)(34). Recent work has demonstrated that BETP functions by forming covalent adducts with Cys-347 in the intracellular loop 3 (ICL3) of GLP-1R, which may mimic a physiological covalent modification (35).…”
Section: Small Molecule Glp-1r Modulators Mimic Endogenous Peptide Homentioning
confidence: 99%